Polar class ship accessibility to Arctic seas north of the Bering Strait in a decade of variable sea-ice conditions - Vlietstra, Lucy S.; Hinrichs, Kayla R.; Bernstein, E. Rachel; Darden, Alexandra; Martino, Matthew (Frontiers in Marine Science, 2023)
Surface atmospheric temperatures over the Arctic Ocean are rising faster than the global average, and sea-ice coverage has declined, making some areas newly accessible to ocean-going ships. Even so, Arctic waters remain hazardous to ships, in part, because of the highly variable nature of sea-ice formation and drift in some areas. In this study, we investigated interannual variability in polar class (PC) ship accessibility in the northern Bering Sea and seas north of the Bering Strait (East Siberian, Chukchi, Beaufort) from February 2012 to February 2022. We used sea-ice charts from the U.S. National Ice Center and calculations of the Risk Index Outcome (RIO) for PC3, PC5, and PC7 ships to characterize spatiotemporal trends in PC ship accessibility during the months of February, June, September, and November over the last 10 to 11 years. We also characterized shipping activity on select days in 2021. Overall, polar class ship accessibility during the months of February and June increased over the last decade, especially for PC7 ships. However, areas that became more accessible over time did not support heavy ship traffic, possibly because they were not located on preferred transit routes or because they were surrounded by unnavigable ice, which made them inaccessible in practice. Ship accessibility was highly variable in the northernmost, offshore regions of the study site. During June, PC7 ship accessibility was interannually variable in waters south of the Bering Strait, and ships were active in those region (most were fishing vessels), indicating potentially hazardous conditions during this time of year. Accessibility was considerably less variable over space and time (months, years) for PC5 (ice capable) ships and for PC3 ships (heavy icebreakers). Information from this study can be used by polar class ship operators planning safe and successful shipping routes and for coastal states preparing emergency services to protect the maritime industry. As governments and the private sector build out fleets of ice-capable ships, knowledge of interannual variability in ship accessibility will also help planners match polar class ship capabilities to mission requirements.